Pengaruh Fasilitas Terminal Penumpang terhadap Kepuasan Pengguna Jasa di Pelabuhan Tanjung Perak - Andhika Sandi Putra Pratama; Bugi Nugraha; Eka Nurmala Sari Agustina; Indah Ayu Johanda Putri (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The Port of Tanjung Perak is intended as the main gateway to connect regions within the country and between countries. With the construction of the GSN Terminal at Tanjung Perak Port, it is hoped that it can be used as access to human mobility so as to provide satisfaction to passengers. The research aims to determine the influence of port facilities consisting of aspects of safety, comfort, convenience and equality on passenger satisfaction. The type of research used in this study is quantitative. This research was carried out at the Port of Tanjung Perak with a time of 1 year. The average daily passenger population in 2024 is 4,593 passengers. The results of the calculation of the Slovin formula can be determined by the number of samples as many as 100 passengers, the data source in this study uses primary and secondary data with data collection techniques, namely: questionnaires, laws and regulations, official government reports, and relevant previous research. The data analysis technique is the Multiple Linear Regression test. The results of this study show that the variables of safety, convenience, and equality in passenger terminal facilities have a positive and significant effect on passenger satisfaction at Tanjung Perak Port. Port facilities have a significant simultaneous effect on passenger satisfaction at Tanjung Perak Port.